Integrating safety elements into post occupancy evaluation for low-cost housing in Malaysia / Husrul Nizam Husin@Husain - Husin@Husain, Husrul Nizam (Institute of Graduate Studies, UiTM, 2016)
The general building conditions in low-cost housing act as an indicator of human quality of life. The enhanced aspects on quality will create a safe environment for the occupants. However, issues arisen have concerning the delivery performance in Malaysia’s low-cost housing since the occupants are likely to perceive safety hazards. The safety issues and challenges during the occupancy period include structural instability and falling building fragments. Without defining the occupants’ requirements in the early housing development, it is hard to determine the prevailing safety factors. To achieve a better safety provision during the occupancy period, this study used the Post Occupancy Evaluation (POE) approach that incorporates participation from the occupants. POE is used to examine specific performance issues in the building occupancy stage. It generally encompasses a comprehensive review of the building’s current situation. The fundamental concept of POE stresses the importance of obtaining feedback from the building occupants. Therefore, the main aim of this research is to develop a Post Occupancy Evaluation (POE) framework that integrates safety elements for low-cost housing (LCH) in Malaysia to meet the occupants’ satisfaction level of LCH. A building inspection survey and occupants’ satisfaction survey was conducted to 24 low cost housing schemes, known as Program Perumahan Rakyat (PPR) housing schemes in Kuala Lumpur, Malaysia. The sample size for both surveys was 380 (380 for housing units; 380 for occupants). Statistical correlation was used to affirm the incorporation of occupants in respect of safety performance in the POE approach. The analysis used Spearman’s rho correlation since the variables in both surveys consist of an ordinal scale…